2023
DOI: 10.1515/commun-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adults’ food media experiences: Preferences, opportunities, and barriers for food literacy promotion

Abstract: This study aims to understand how and why emerging adults come into contact with food media messages, and what they perceive as positive and negative outcomes related to food literacy. Seven focus groups, stratified by gender and socio-economic status, with 37 emerging adults aged between 18 and 25 were conducted. Photovoice was used to reflect on participants’ real-life food media experiences. Findings reveal that food media consumption is a combination of actively searching and incidentally encountering. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, previous research has mainly focused on investigating how emerging adults perceive social media recipes (e.g. Wang et al, 2022), from which we can also deduce how recipes may contribute to food literacy (Decorte et al, 2022;Steils and Obaidalahe, 2020;Teunissen et al, 2023;Vaterlaus et al, 2015;Wang et al, 2022). Here, the research found that emerging adults perceive recipes on social media as an important source of education related to various food literacy components (i.e.…”
Section: References To Food Literacy Aspectsmentioning
confidence: 91%
See 3 more Smart Citations
“…However, previous research has mainly focused on investigating how emerging adults perceive social media recipes (e.g. Wang et al, 2022), from which we can also deduce how recipes may contribute to food literacy (Decorte et al, 2022;Steils and Obaidalahe, 2020;Teunissen et al, 2023;Vaterlaus et al, 2015;Wang et al, 2022). Here, the research found that emerging adults perceive recipes on social media as an important source of education related to various food literacy components (i.e.…”
Section: References To Food Literacy Aspectsmentioning
confidence: 91%
“…Within this specific demographic, recipe-related content from food influencers (i.e. food celebrities who focus primarily on food-related topics; Goodman and Jaworska, 2020) has been found to be popular (Bramston et al, 2020;Teunissen et al, 2023). However, the extent to which this recipe-related content from food influencers reflects the different aspects of food literacy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging adults often face barriers such as insufficient resources and the unavailability of required ingredients or kitchen materials to prepare meals (Howse et al, 2018;Malan et al, 2020;Sogari et al, 2018). Additionally, they often experience that available recipes may require ingredients or kitchen materials that are not readily available (Teunissen et al, 2023), as such it is necessary for emerging adults to learn how to make meals with the resources they have available and to adapt recipes as needed (e.g., substitute ingredients or modify cooking methods based on what they have available).…”
Section: Essential Food Literacy Competenciesmentioning
confidence: 99%